2022
DOI: 10.4236/ojbm.2022.101018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Packaging on Perceived Quality and Brand Loyalty: The Mediating Role of Brand Association in Over-the-Counter Market

Abstract: Distinctive packaging design and strong brand association are essential elements to increase brand quality and customer loyalty which can insulate a company against competitive actions in a retail environment. However, there is a relative scarcity of studies on the impact of packaging on brand quality and loyalty through the mediating effect of brand association in the overthe-counter health market. Against this background, the current study aimed to investigate the packaging's effect on brand quality and loya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 32 publications
2
15
0
3
Order By: Relevance
“…The results of the study show that packaging has a positive and significant effect on the medicinal herbal product quality in the drug industry. This result is consistent with previous studies (Underwood & Klein, 2002;Wang, 2013;Mensah et al, 2022), which indicate that packaging has a significant influence on product quality. This implies that the quality of the medicinal herbal product is reflected in the quality of its packaging.…”
Section: Discussion Of Findingssupporting
confidence: 93%
See 4 more Smart Citations
“…The results of the study show that packaging has a positive and significant effect on the medicinal herbal product quality in the drug industry. This result is consistent with previous studies (Underwood & Klein, 2002;Wang, 2013;Mensah et al, 2022), which indicate that packaging has a significant influence on product quality. This implies that the quality of the medicinal herbal product is reflected in the quality of its packaging.…”
Section: Discussion Of Findingssupporting
confidence: 93%
“…The author also stated that perceived quality is a key indicator of user satisfaction which drives future buying decisions and customer loyalty. Furthermore, earlier studies reported that perceived quality positively influences brand equity (Yoo et al, 2000;Buil et al, 2013) and brand loyalty (Hyun & Kim, 2011;Gil et al, 2007;Mensah et al, 2022), and in turn, perceived quality is positively and significantly affected by packaging (Underwood & Klein, 2002;Wang, 2013;Mensah et al, 2022).…”
Section: Customer-based Brand Equitymentioning
confidence: 97%
See 3 more Smart Citations